PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH PERTANIAN DI DESA PENGALANGAN KABUPATEN GRESIK - Prisma Tri Hardani; Intan Ayu Kusuma Pramushinta; Asti Rahayu; Tatang Sopandi; Muhammad Ali Hadi Firmansyah; Chafid Izuddin; Ahmad Rizky Pratama; Adella Eka Berliyanti; Indra Dwi Framono (LP2M STP Mataram, 2023)
Farmers' use of chemical fertilizers to increase agricultural production has become quite popular in today's technological era. However, considering the negative impact of chemical fertilizers, alternatives are needed so that farmers can reduce the use of chemical fertilizers and switch to organic fertilizers or biological fertilizers. Seeing this, we realized that Pengalangan Village had the potential to develop this, considering that the agricultural sector was their primary sector. Therefore, to realize this immediately, it is necessary to provide training for residents. The methods used in this training activity were the presentation of material, distribution of modules, question and answer sessions and discussions, practicing making organic fertilizer, and completing pre-tests and post-tests. After the training activity ends, an evaluation is carried out using data collected through pre-test and post-test. Based on the research results and discussion regarding pre-test and post-test data, it can be concluded that the presentation of the material significantly influences residents' level of knowledge regarding liquid organic fertilizer (POC).